Influence of Hypothermia and Cell Therapy on Structural Changes in Brain Tissues of Rats with Dyscirculatory Encephalopathy of Mixed Genesis - Babiychuk, Vladyslav; Aidarova, Viktoria; Lomakin, Ivan; Kudokotseva, Olga; Roy, Nataliia; Naumova, Olga; Protsenko Оlena (Problems of Cryobiology and Cryomedicine, 2021)
The study examines the morphological changes that occur in brain of SHR rats on the background of developing hypertensive dyscirculatory encephalopathy (DE), complicated by chronic alcohol intoxication (CAI). CAI has been proven to potentiate the progressive aging of brain in rats with hypertensive DE by aggravating its course and to lead to the development of DE of mixed genesis. The effectiveness of a single and combined use of rhythmic craniocerebral hypothermia (rCCH) and the introduction of cryopreserved cord blood nucleated cells (cCBNCs) to reduce the progressive vascular lesions of brain and the effects of chronic ischemia in animals with DE of mixed genesis. It has been proven that the combined use of rCCH and cCBNCs in the rats with a mixed DE had a more pronounced positive effect on morphological structure of brain tissues and vessels than their single use. There was a further decrease in the signs of dystrophic, destructive and pathologically altered compensatory adaptive processes in brain on the background of a significant decrease in neuroglial index, stimulation of angiogenesis, complete or partial absence of signs of smooth muscle cell hyperplasia, acute hemorrhages and ischemic strokes, spasms of arterial vessels’ walls and plethory in veins, that contributed to restoration of brain microhemocirculation and cytoarchitectonics. Probl Cryobiol Cryomed 2021; 31(2): 151–160